2003
DOI: 10.1182/blood-2003-04-1114
|View full text |Cite
|
Sign up to set email alerts
|

Signaling through JAM-1 and αvβ3 is required for the angiogenic action of bFGF: dissociation of the JAM-1 and αvβ3 complex

Abstract: Growth factor–induced neovascularization has received a great deal of attention because it is fundamental to the growth and metastasis of solid tumors. This multistep process requires extensive signaling through growth factor receptors and integrins. Among the integrins involved in this process, integrin αvβ3 is specific to basic fibroblast growth factor (bFGF)–induced angiogenesis. Here we show that junctional adhesion molecule 1/A (JAM-1/A) and αvβ3 form a complex in the absence of bFGF. JAM-1, which is norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
112
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 129 publications
(125 citation statements)
references
References 39 publications
11
112
0
2
Order By: Relevance
“…65e67 An interesting feature of this family of proteins are the tissue-specific functions that seem to be governed by protein distribution patterns and may account for the wide variety of observed functions attributed to various JAMs. A few of the reported functions include regulation of epithelial barrier, 68,69 endothelial and epithelial cell migration, 70,71 spermatogenesis, 72 angiogenesis, 73 and leukocyte adhesion. 74 In addition, JAMs have been linked to roles in the pathophysiology of several disease processes, such as atherosclerosis, 75,76 cancer metastasis, 77 and IBD.…”
Section: Neutrophils Engage Basolateral Epithelial Receptors During Tmentioning
confidence: 99%
“…65e67 An interesting feature of this family of proteins are the tissue-specific functions that seem to be governed by protein distribution patterns and may account for the wide variety of observed functions attributed to various JAMs. A few of the reported functions include regulation of epithelial barrier, 68,69 endothelial and epithelial cell migration, 70,71 spermatogenesis, 72 angiogenesis, 73 and leukocyte adhesion. 74 In addition, JAMs have been linked to roles in the pathophysiology of several disease processes, such as atherosclerosis, 75,76 cancer metastasis, 77 and IBD.…”
Section: Neutrophils Engage Basolateral Epithelial Receptors During Tmentioning
confidence: 99%
“…It has been reported previously that JAM-A regulates epithelial and endothelial cell migration (Naik et al, 2003a;Bazzoni et al, 2005;Severson et al, 2008). To confirm that JAM-A regulates cell migration in SKCO-15 cells, we evaluated the effect of decreased JAM-A protein levels on wound closure in a scratch wound assay.…”
Section: Jam-a Regulates Epithelial Cell Migration Through Afadin Butmentioning
confidence: 99%
“…In these cells, JAM-A has been reported to play a role in the regulation of epithelial barrier function (Mandell et al, 2005;Laukoetter et al, 2007), endothelial cell migration (Naik et al, 2003a;Bazzoni et al, 2005), angiogenesis (Naik et al, 2003a), platelet aggregation (Babinska et al, 2002), and leukocyte adhesion (Martin-Padura et al, 1998;Del Maschio et al, 1999). Recent reports suggest that JAM-A not only directly decreases paracellular permeability (Mandell et al, 2005;Laukoetter et al, 2007) but also promotes epithelial cell migration (Severson et al, 2008), which is critical for the maintenance of intestinal barrier in health and disease (Lacy, 1988;Fenteany et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…We also hypothesize that endothelial P2Y 2 R relocation to adherens junctions assists in the transient disruption of endothelial junctions and escorts leukocytes to endothelial borders for paracellular diapedesis, possibly through association of the P2Y 2 R with the α V β 3 integrin. This integrin is known to form a complex with the P2Y 2 R [23] and with JAM-1 [276], a junctional adhesion molecule in endothelial cells that interacts with the leukocyte integrin, LFA-1, and is important for both leukocyte adhesion and diapedesis [277] activation [73]; and the upregulation of tissue factor, an initiator of platelet aggregation [260]. Recently, we found that activation of the P2Y 2 R in human coronary artery endothelial cells causes a rapid translocation of the receptor to cell-cell junctional zones where it interacts with VEcadherin (unpublished results), a protein found specifically in endothelial adherens junctions that is important for maintaining the vascular permeability barrier.…”
Section: Proinflammatory P2y 2 R Functions In Endotheliummentioning
confidence: 99%